Psychosemantic analysis of the concept of manager’s competence - Malimon, Liudmyla; Pashkinа, Alla; Малімон, Людмила; Пашкіна, Алла (My University, 2019)
The article deals with the psychosemantic reconstruction of the concept of manager’s competence. The study is based on free word association test (WAT) held with the managers of public administration (n=38) from Volyn Oblast (Ukraine) and master candidates of the public administration program (n=38) who studied at Eastern European National University in Lutsk (Ukraine). Nuclear zones, single frequency responses, and associative field structure of the investigated concept in the two samples were analyzed. The most frequent nuclear associations confirmed the lexicographic meaning of the concept “competence” and revealed that the leader’s expertise is closely related to their professional knowledge and skills. Next, factor analysis of data obtained from the Semantic Differential (SD) test established common and distinctive features of the semantic field structure of the concept of manager’s competence. The research results showed that the managers from the sample emphasized the importance of experience and effectiveness, the development of their professionally relevant job skills and ability to influence their subordinates. By contrast, master candidates, along with experience and job skills, indicated a set of characteristics that demonstrate the need for a general intellectual level of the managers, their moral and ethical personality traits, and their ability to maintain effective interpersonal interaction.Статтю присвячено психоcемантичній реконструкції концепту «управлінська компетентність». Дослідження здійснено на основі методу вільного асоціативного експерименту, проведеного з 38 менеджерами державної служби Волинської області (Україна), а також 38 здобувачами ступеня магістра освітньо-професійної програми «державна служба». Проаналізовано ядерні зони, реакції з одиничною частотністю та структуру асоціативних полів досліджуваного концепту у двох вибірках. Виокремлено найчастотніші ядерні асоціації, які підтвердили лексикографічне значення слова «компетентний» і пов’язують компетентність керівника з його професійними знаннями й уміннями. Зіставлено результати факторного аналізу даних семантичного диференціалу. Підсумком є з’ясування спільних і відмінних ознак у структуруванні семантичних полів концепту «управлінська компетентність»: керівники державної служби підкреслюють важливість досвіду й результативності діяльності керівника, розвитку його професійно важливих управлінських якостей і здатності впливати на інших. Натомість, студентимагістри, поряд із досвідом та результативністю праці, виокремлюють групи характеристик, що засвідчують потребу загального інтелектуального рівня керівника, розвитку його морально-етичних особистісних рис та вміння налагоджувати ефективну міжособистісну взаємодію
Психосемантичний аналіз концепту «управлінська компетентність
Keywords: psychosemantic analysis; manager’s competence; concept; public administration; free word association test; semantic differential; психосемантичний аналіз; управлінська компетентність; концепт; державна служба; вільний асоціативний експеримент; семантичний диференціал